Standards for designing a program for conceptual maps based on integrated learning in developing jurisprudential concepts for Non-Native Arabic learners; from the point of view of instructors - Alodaini, Ahmed Mahyoub; Salem, El-Sayed Mohamed (Journal of Humanities & Social Sciences, 2021)
This research aims to present the necessary concepts of jurisprudence and to prepare standards for electronic concept maps based on integrated learning in the development of jurisprudential concepts.To achieve these aims, the researcher prepared a list of the necessary jurisprudential concepts, and a list of standards for the electronic concept maps program based on integrated learning in the development of jurisprudential concepts.The research used the descriptive approach, and it has reached the following results: A list of jurisprudential concepts, which included the field of Umrah and Hajj, and it contained (8) main concepts, from which (34) sub-concepts emerged, (5) main standards, and from them (33) sub-indicators emerged from the electronic concept maps program based on integrated learning in the development of jurisprudential concepts for Non-Native Arabic learners.In light of the results reached, the researcher presented a number of recommendations and suggestions.
Keywords: Arabic learners from non-native speakers; concept maps; blended learning; jurisprudential concepts; study students